Revealing the Heterogeneity of Large‐Area MoS2 Layers in the Electrocatalytic Hydrogen Evolution Reaction. Issue 17 (8th September 2022) - Schumacher, Simon; Madauß, Lukas; Liebsch, Yossarian; Tetteh, Emmanuel Batsa; Varhade, Swapnil; Schuhmann, Wolfgang; Schleberger, Marika; Andronescu, Corina
Abstract: The electrocatalytic activity concerning the hydrogen evolution reaction (HER) of micrometer‐sized MoS2 layers transferred on a glassy carbon surface was evaluated by scanning electrochemical cell microscopy (SECCM) in a high‐throughput approach. Multiple areas on single or multiple MoS2 layers were assessed using a hopping mode nanocapillary positioning with a hopping distance of 500 nm and a nanopipette size of around 55 nm. The locally recorded linear sweep voltammograms revealed a high lateral heterogeneity over the MoS2 sheet regarding their HER activity, with currents between −40 and −60 pA recorded at −0.89 V vs. reversible hygrogen electrode over about 4400 different measured areas on the MoS2 sheet. Stacked MoS2 layers did not show different electrocatalytic activity than the single MoS2 sheet, suggesting that the interlayer resistance influences the electrocatalytic activity less than the resistances induced by possible polymer residues or water layers formed between the transferred MoS2 sheet and the glassy carbon electrode. Abstract : Heterogeneity of MoS2 in HER : The catalytic activity for the hydrogen evolution reaction (HER) of large‐area MoS2 sheets transferred in a wet process was analysed by means of scanning electrochemical cell microscopy. A lateral heterogeneity of the activity on the MoS2 sheets could be revealed. However, no discernable differences were recorded between single‐layer MoS2 and multi‐layer MoS2 .